Body image and disordered eating prevention in girls' sport: A partner-driven and stakeholder-informed scoping review of interventions. (July 2022) - Sick, Kelsey; Sabiston, Catherine M.; Maharaj, Aryel; Pila, Eva
Abstract: Despite the evidenced benefits of participating in organized sport, adolescent girls consistently report lower rates of sport participation, worse sport experiences, and higher dropout rates, compared to boys. Body image concerns have been linked to this gender disparity and established as a critical predictor of disordered eating, thus necessitating effective prevention efforts to mitigate the negative impacts of body image concerns and disordered eating for adolescent girls. In partnership with the National Eating Disorder Information Centre (NEDIC; Canada), the present scoping review was conducted to examine the nature and characteristics of sport-specific body image and disordered eating interventions for adolescent girls. Fourteen studies were identified through various search strategies. Over half of the studies demonstrated modest yet worthwhile effects on various body image and disordered eating outcomes. Intervention characteristics (i.e., frequency, modes of delivery, topics, material, outcomes measured) varied across initiatives. Fifty-nine national, provincial, and local sport system representatives were consulted as stakeholders and provided practical input to the results of the scoping review. Sport stakeholders favoured the delivery of a multidimensional, multicomponent program, with a combination of evidence-based techniques. This synthesis of knowledge will shape the development and dissemination of future programs, and contribute to the development of equitable sport participation opportunities for Canadian girls. Highlights: First review to align evidence-based strategies with stakeholders' perspectives. 14 studies targeted body image and disordered eating interventions in girl sports. No clear pattern of effective interventions favouring any one particular method. 59 stakeholders from community, provincial, and national organizations contributed. Sport stakeholders prefer a blended delivery model with a combination of techniques.